VEGETABLE GROWING IN THE FOOD MARKET SYSTEM: PECULIARITIES, TENDENCIES, PROSPECTS (INNOVATIVE ECONOMY, 2021)
Rud V.P. VEGETABLE GROWING IN THE FOOD MARKET SYSTEM: PECULIARITIES, TENDENCIES, PROSPECTSPurpose. The aim of the article is the analysis of the current state of vegetable production in Ukraine, identification of the main problems of its development, identification of areas for stabilization and improving the efficiency of the vegetable sub-complex in the future.Methodology of research. The methodological basis of the study was scientific papers on the formation and functioning of the vegetable market. The following methods were used: dialectical, abstract and logical, system analysis (theoretical generalizations and conclusions); mathematical and statistical, the method of expert assessments (when establishing a rating assessment of the level of vegetable yield).Findings. The analysis of production indicators, sown areas and yield levels of major crops for the period 2000-2019 in Ukraine, Europe and the world was carried out. The peculiarities of the development of the vegetable sub-complex in the system of the national food market are determined. Aspects of formation of food security of Ukraine on the basis of an estimation of levels of manufacture and consumption, volumes of export and import are considered. The level of food security of the country in 2015 and 2019 was determined by calculating the indicator of economic affordability of products and indicators of adequacy of consumption of different groups of products in Ukraine in 2019. The reasons of unsatisfactory condition of the vegetable sub-complex are analysed, the general strategy and priority directions of development of vegetable growing and melon growing and processing branch for the period till 2025 are stated.Originality. The study of trends in the development of the vegetable industry for the 20-year period (2000-2019) in Ukraine, CIS countries, regions of the world and a comparison of the rate of change of these indicators for this period was further developed.Practical value. The results of the conducted study can be used in the development of sectoral and regional strategic policy documents for the development of vegetable growing, as well as agricultural enterprises in determining further guidelines for their own development.Key words: food security, vegetable growing, production dynamics, consumption, innovative development.
Keywords: Key words; food security; vegetable growing; production dynamics; consumption; innovative development.